Penerapan Teks Berjalan Sebagai Media Informasi Sekolah - Herdianto, Herdianto; Ramadhan, Syahrul (LKP KARYA PRIMA KURSUS, 2024)
One of the problems currently being faced by Imelda Vocational School is the lack of knowledge of students and teachers regarding microcontrollers and the limited budget for school promotion. Therefore, the goal to be achieved from this service is to increase the knowledge of Imelda School students/teachers regarding what a microcontroller is and the various applications that can be made from microcontrollers, including running text which can later be used as a medium to introduce the school to the community. To accelerate the achievement of service goals, approaches are made to related parties such as school principals and teachers who will later be involved as coordinators of the service team. In order to complete it according to the predetermined schedule, the team has prepared service steps such as field observations, identifying problems, determining the right solution, conducting training and evaluation. From the results of the questions and answers that have been conducted with the training participants, it is known that the service that has been carried out has increased the knowledge of the training participants.